Comparative evaluation of fracture resistance of endodontically treated maxillary premolars restored with three different fibre-reinforced composites: An in vitro study - Jagapathi Babu Mavidi; K. Madhu Varma; Girija S. Sajjan; R. Kalyan Satish; Lokesh Dasari; Katyayani Ajjimera (Endodontology, 2025)
Aim: The aim of this research was to evaluate the reinforcement of endodontically treated maxillary premolars with mesio-occluso-distal (MOD) cavities using three different fiber-reinforced composite (FRC) resins. Methods: Sixty extracted human maxillary premolars were used (n = 12). Group I served as positive control. From Group II–V, root canal treatment is followed by the preparation of standardized MOD cavities. Group II (NH): Teeth were restored with nanohybrid composite resin as a negative control, Group III (OF): Teeth were restored with nanohybrid composite resin incorporating polyethylene fiber within the occlusal groove, Group-IV (EXP): Teeth were restored with short FRC resin followed by nanohybrid composite resin, Group V (FFC): teeth were restored with Fibrafill cube followed by nanohybrid composite resin. Following thermocycling, the fracture resistance of the samples was tested with a universal testing machine (UTM) and measured in Newtons. The data were compiled and arranged in tables for statistical analysis. Kolmogorov–Smirnov test, one-way analysis of variance, Tukey’s post hoc test, and Chi-square test were employed in this study. Results: The fracture resistance of the OF, EXP, and FFC groups was significantly higher than that of the NH group (P < 0.05). Furthermore, the OF and EXP groups showed significantly higher fracture resistance than the FFC group (P < 0.05), with no significant difference between OF and EXP. Fracture patterns did not significantly vary among the study groups (P > 0.05). Conclusion: Endodontically treated maxillary premolars restored with Ribbond (OF) and short FRC resin (EXP) exhibited superior fracture resistance with favorable fracture patterns and might be considered as conservative approach for reinforcing ETT.